TaÊ¼thÄ«r IstikhdÄm IstirÄtÄ«jÄ«yah TadrÄ«s al-AqrÄn (Peer Lessons) fÄ« NatÄÊ¿ij TaÊ¿lÄ«m al-Lughah al-Ê¿ArabÄ«yyah - Putri, Dhayana (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The problems in this research are student learning outcomes are low, students are less interested in learning Arabic, teachers teaching Arabic still do not use traditional teaching strategies, and the teaching process in the classroom is focused on teachers and not on students. The purpose of this research is: 1) To find the effect of the use of peer lessons strategy on student learning outcomes, 2) To find the extent to which the effect of the use of peer lessons strategy on student learning outcomes. This research method used is a quasi-experiment with a non-equivalent control group design. The population is all 10th-gradeÂ students and the sampling technique is purposive sampling. Data collection was carried out using test results in the form of multiple-choice questions. The result of the research based on the independent sample t-test analysis is: 1) There is an effect of peer lessons strategy on student learning outcomes because, in the Independent Sample t-test, sig values were obtained the value of sig. (2-tailed)0.001 > Î±.(0.05). 2) The effect of peer lessons strategy on student learning outcomes of 42.59 %.ÙŠÙ†Ø·Ù„Ù‚ Ø§Ù„Ø¨ØØ« Ù…Ù† Ø§Ù„Ù…Ø´ÙƒÙ„Ø§Øª Ø§Ù„ØªÙŠ ØªÙˆØ§Ø¬Ù‡ Ø·Ù„Ø§Ø¨ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¹Ø§Ø´Ø± Ø¨Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© 4 Ø¢ØºØ§Ù…. Ùˆ Ù…Ù†Ù‡Ø§ Ù†ØªØ§Ø¦Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ø·Ù„Ø§Ø¨ Ù…Ù†Ø®ÙØ¶Ø©ØŒ ÙˆÙ‚Ù„Ø© Ø§Ù„Ø§Ù‡ØªÙ…Ø§Ù… Ø·Ù„Ø§Ø¨ Ø¨ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ Ù„Ù… ÙŠØ²Ù„ Ø§Ù„Ù…Ø¹Ù„Ù… ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠØ© ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ØŒ ÙˆØªØ±ÙƒØ² Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø¹Ù„Ù… ÙˆÙ„Ù… ØªØªØ±ÙƒØ² Ø¹Ù„Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨. Ø£Ù…Ø§ Ø£Ù‡Ø¯Ø§Ù Ø§Ù„Ø¨ØØ« Ù‡ÙŠ: Ù„Ù…Ø¹Ø±ÙØ© Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ø£Ù‚Ø±Ø§Ù† (Peer Lessons) ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆÙ„Ù…Ø¹Ø±ÙØ© Ù†ØªØ§Ø¦Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆÙ„Ù…Ø¹Ø±ÙØ© ØªØ£Ø«ÙŠØ± Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ø£Ù‚Ø±Ø§Ù† (Peer Lessons) Â ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ø¯Ø±Ø³Ø©. Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙ…ÙŠ Ø¨Ù†ÙˆØ¹ ØªØ¬Ø±Ø¨ÙŠ Ø²Ø§Ø¦ÙÙŠØŒ ÙˆØªØµÙ…ÙŠÙ… Ø§Ù„Ø¨ØØ« Ù‡Ùˆ ØªØµÙ…ÙŠÙ… Nonequivalent Control Group Design. ÙˆØ§Ù„Ù…Ø¬ØªÙ…Ø¹ Ù„Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø¬Ù…ÙŠØ¹ Ø§Ù„Ø·Ù„Ø§Ø¨ ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¹Ø§Ø´Ø± ÙˆØ§Ù„Ø¹ÙŠÙ†Ø© ÙŠØ¹Ù†ÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„Ø¶Ø§Ø¨Ø· (X Mipa 2) ÙˆØ§Ù„ÙØµÙ„ Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠ (X Mipa 1) Ø¨ØªÙ‚Ù†ÙŠØ© Ø£Ø®Ø° Ø§Ù„Ø¹ÙŠÙ†Ø© Ù‡ÙŠ Purpossive sampling.Â ØªÙ… Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø§Ø®ØªØ¨Ø§Ø± ÙÙŠ Ø´ÙƒÙ„ Ø£Ø³Ø¦Ù„Ø© Ø§Ù„Ø§Ø®ØªÙŠØ§Ø± Ù…Ù† Ù…ØªØ¹Ø¯Ø¯. Â Ø¨Ù†Ø§Ø¡ Ø¹Ù„Ù‰ Ù†ØªØ§Ø¦Ø¬ Ø§Ø®ØªØ¨Ø§Ø± Ø§Ù„ÙØ±Ø¶ÙŠØ§Øª ÙÙŠ SPSS Ø§Ù„Ù†ØªÙŠØ¬Ø© Ø§Ù„Ø£Ù‡Ù…ÙŠØ© Ø£Ùˆ Sig.(2-Tailed) ÙÙŠ Ø¬Ø¯ÙˆÙ„ Independent Sampel T Test Â Ù‡ÙŠ 0ØŒ001 Ø£ØµØºØ± Ù…Ù† 0.05 ÙØ§Ù„Ù…Ù‚Ø¨ÙˆÙ„ ÙØ±Ø¶ÙŠØ© Ø¨Ø¯Ù„ÙŠØ©.Â